2021
DOI: 10.1111/codi.15515
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the Memorial Sloan Kettering Bowel Function Instrument and the Low Anterior Resection Syndrome Questionnaire for assessment of bowel dysfunction in rectal cancer patients after low anterior resection

Abstract: Aim Neoadjuvant therapy and total mesorectal excision (TME) for rectal cancer are associated with bowel dysfunction symptoms known as low anterior resection syndrome (LARS). Our study compared the only two validated instruments—the LARS Questionnaire (LARS‐Q) and the Memorial Sloan Kettering Bowel Function Instrument (MSK‐BFI)—in rectal cancer patients undergoing sphincter‐preserving TME. Methods One hundred and ninety patients undergoing sphincter‐preserving TME for Stage I–III rectal cancer completed the MSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Although the two instruments may measure the same construct, the cohorts used to develop the instruments differed significantly in terms of clinical factors, such as tumor level and surgical techniques. Recent studies have confirmed good correlation and similar discriminant validity of these two questionnaires ( 30 , 31 ). An additional limitation of our study is that it is a single-center study focused on patients treated by highly subspecialized surgeons who are sought out for their technical skill and their ability to perform sphincter preservation for ultralow tumors, with 26% of SPS anastomoses being handsewn.…”
Section: Discussionmentioning
confidence: 64%
“…Although the two instruments may measure the same construct, the cohorts used to develop the instruments differed significantly in terms of clinical factors, such as tumor level and surgical techniques. Recent studies have confirmed good correlation and similar discriminant validity of these two questionnaires ( 30 , 31 ). An additional limitation of our study is that it is a single-center study focused on patients treated by highly subspecialized surgeons who are sought out for their technical skill and their ability to perform sphincter preservation for ultralow tumors, with 26% of SPS anastomoses being handsewn.…”
Section: Discussionmentioning
confidence: 64%
“…First, it is limited by its single-institution nature with a relatively small sample size. Second, the Memorial Sloan Kettering Bowel Function Instrument was not used in this series because it showed similar discriminative validity for bowel dysfunction with the LARS score, 35 and, hence, their associations with QoL were not determined. Indeed, more than 100 items within the aforementioned questionnaires were too lengthy and complex for patients to complete in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, LARS score is a concise PROM, and it has proven to have good psychometric properties with robust internal consistency, repeatability, and discriminant validity compared to other bowel function tools and seems to be a valid instrument for measuring bowel dysfunction in the long term. 37,38…”
Section: Discussionmentioning
confidence: 99%